Phytochemical profile and functionality of Brassicaceae species. (August 2020) - Fusari, Cecilia M.; Nazareno, Mónica A.; Locatelli, Daniela A.; Fontana, Ariel; Beretta, Vanesa; Camargo, Alejandra B.
Abstract: The most widely consumed Brassicaceae species were characterized and compared in the present study. The isothiocyanates and phenolic profiles were measured. The in vitro antioxidant and antiradical activities were determined using 2, 2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid diammonium salt, 1, 1-diphenyl-2-picrylhydrazyl radical, ferric reducing antioxidant potential and β-carotene methods. The results showed that all Brassicaceae species evaluated had antioxidant properties, with watercress and green mustard being the most active antioxidant species. Every vegetable studied had a unique sulfur and phenolic profile. Twenty-five phytochemicals were found in Brassicaceae species and their antioxidant activity measured using pure compounds. The results showed that the strongest antioxidant compounds in decreasing order were myricetin, quercetin-3-galactoside, quercetin-3-glucoside, pterostilbene, ferulic acid, kaempferol, allyl isothiocyanate, and (-)-epicatechin. Besides, the phenolic compound trans -resveratrol was found in these species. The highest concentration of trans -resveratrol was observed in rocket leaves at up to 84 μg/g dry weight. Graphical abstract: Image 1 Highlights: Bioactive phytochemicals in 9 cruciferous species were investigated. Twenty five phytochemicals were quantified. All species analyzed show antioxidant activity. Each cruciferous vegetable had its own phenolic and sulfur compound profile. Cruciferous vegetables are a sources of trans-resveratrol.